Transcriptome analysis of shade-induced growth and photosynthetic responses in soybean cultivars - Fengyi Zhang; Runnan Zhou; Rongqiang Yuan; Xiao Zhu; Xinyue Zhang; Sobhi F. Lamlom; Dai Shi; Ahmed M. Abdelghany; Jidao Du; Honglei Ren; Lijuan Qiu (PLoS ONE, 2025)
Shade stress alters soybean growth through transcriptomic changes and adaptive responses that optimize light capture and utilization, regulated by a phytohormonal network. This study examined the physiological, morphological, and molecular responses of Guru (shade-tolerant) and Heinong 53 (shade-sensitive) soybean cultivars under 0% (control), 30%, and 70% shade. Results revealed morphological responses where Heinong 53 exhibited greater plant height (52.8 cm) compared to Guru (45.2 cm) under 30% shade. However, physiological responses favored Guru, with higher chlorophyll content under both 30% shade (2.8 mg/g vs 2.1 mg/g) and 70% shade (2.5 mg/g vs 1.6 mg/g). Guru also demonstrated superior photosynthetic performance, with higher net photosynthetic rates under control conditions (18.5 vs 15.2 µmol CO₂/m2/s) and under 70% shade (12.4 vs 8.7 µmol CO₂/m2/s). Transcriptome analysis identified 2,596 differentially expressed genes (DEGs) across nine comparison groups, with 279 up-regulated and 388 down-regulated genes common across shade treatments. Significant DEGs were associated with shade avoidance (GO:0009641), programmed cell death (GO:0012501), and shoot development (GO:0010223). Key molecular functions included histone deacetylase activity and calcium-dependent protein kinase (GO:0009931). Gene-trait correlations revealed 37 up-regulated DEGs positively correlated with photosynthesis-related metrics, while 28 were negatively correlated with transpiration rate. Additionally, 12 DEGs positively correlated with plant height, and 6 down-regulated DEGs negatively correlated with photosynthetic characteristics. Overall, the cultivar Guru exhibited effective resource allocation, maintained robust photosynthetic activity, and displayed consistent gene expression patterns under shade stress, revealing key mechanisms of soybean shade tolerance. These findings advance the development of shade-resilient soybean cultivars and offer strategies to enhance crop productivity in low-light environments.